Civilizing the child : discourses of race, nation, and child welfare in America - Bullard, Katharine S., 1974- (Lexington Books, 2013)
In Civilizing the Child: Discourses of Race, Nation and Child Welfare in America, Katherine S. Bullard analyzes the discourse of child welfare advocates who argued for the notion of a racialized ideal child. This ideal child, limited to white, often native-born children, was at the center of arguments for material support to children and education for their parents. This text illuminates important limitations in the Progressive approach to social welfare and helps to explain the current dearth of support for poor children.